Effect of Tibial Plateau Angle on Cranial Cruciate Ligament Strain: An Ex Vivo Study in the Dog. Issue 1 (6th June 2014) - Haynes, Kevin H.; Biskup, Jeffrey; Freeman, Andrew; Conzemius, Michael G.
<x xml:space="preserve">Abstract</x> Objective To evaluate the relationship between tibial plateau angle (TPA) and strain in the intact cranial cruciate ligament (CCL) during axial loading. Study Design Ex vivo mechanical testing study. Sample Population Cadaveric canine stifles (n = 6). Methods A bicentric and uni‐radial Slocum saw blade was used to perform the osteotomy on each stifle and a custom designed plate was secured to the leg. Each stifle was loaded and CCL strain and axial displacement were recorded. TPA was adjusted to −20°, −10°, 0°, +10°, +20° of normal. Change in the strain was assessed during the axial loading period. Results For all specimens, linear displacement of the femur and CCL strain increased with increasing axial load. Mean change in strain was 4.41, 5.26, 6.02, 6.3, and 7.39 at −20°, −10°, 0°, 10°, and 20°, respectively. The R‐squared for the linear regression equation was 0.91, suggesting a strong relationship between change in TPA and CCL strain. Conclusions The mechanical testing model used found CCL strain increased with increasing axial load regardless of the TPA. Decreasing TPA decreased strain in the intact CCL.